Aging of the Suprachiasmatic Clock. (February 2014) - Farajnia, Sahar; Deboer, Tom; Rohling, Jos H. T.; Meijer, Johanna H.; Michel, Stephan
More than half of the elderly in today's society suffer from sleep disorders with detrimental effects on brain function, behavior, and social life. A major contribution to the regulation of sleep stems from the circadian system. The central circadian clock located in the suprachiasmatic nucleus of the hypothalamus is like other brain regions subject to age-associated changes. Age affects different levels of the clock machinery from molecular rhythms, intracellular messenger, and membrane properties to neuronal network synchronization. While some of the age-sensitive components of the circadian clock, like ion channels and neurotransmitters, have been described, little is known about the underlying mechanisms. In any case, the result is a reduction in the amplitude of the circadian timing signal produced by the suprachiasmatic nucleus, a weakening in the control of peripheral oscillators and a decrease in amplitude and precision of daily rhythms in physiology and behavior. The distortion in temporal organization is thought to be related to a number of serious health problems and promote neurodegeneration. Understanding the mechanisms underlying age-related deficits in circadian clock function will therefore not only benefit rhythm disorders but also alleviate age-associated diseases aggravated by clock dysfunction.